Matthew the Lord’s disciple communicates his justification of Mary as the Mother of the Messiah - Dr. Mike Megrove Reddy (Pharos Journal of Theology, 2020)
Genealogies were in the past written so as to show lineage of people who were significant in society. However, in recent times many individuals want to discover about their family tree. When the writer of the Gospel of Matthew laid out the genealogy of Christ the Messiah, he started from Abraham. He did this because Abraham was regarded as the father of the Jewish nation. Therefore, it implies that the writer was writing with the intention of reaching a Jewish audience. It could therefore be assumed that the writer used written communication to persuade the Jews that Jesus is the Messiah and the one spoken of in the Old Testament by the prophets. However, he realised that many Jews had and are still having reservations in believing that Mary could be a chosen vessel because they did not then or presently see her as a virtuous and pure woman. Like an advocate who uses supplementary information and facts to build a case before he/she can defend his/her client, so too does the writer of the gospel of Matthew mention four women’s names before he can present Mary in his genealogy. This was to signify that if those women could be in the lineage of Judah, why could Mary not be qualified to bring forth the Messiah? The theoretical framework for this paper is the Shannon and Weaver Model of Communication. The objective of this paper was to show how written communication was used to substantiate that Mary is the mother of the Messiah.